IMPLEMENTATION OF ISLAMIC POLITICAL ETHICS IN INDONESIA: STUDY OF IBN KHALDUN'S THOUGHTS - M. Yusran S; Azizah, Nurul; M. Hairul; Kurniati (Archipelago Journal of Southeast Asia Islamic Studies, 2024)
This research is entitled "Implementation of Islamic Political Ethics in Indonesia (A Study of Ibnu Khaldun's Thought)" which aims to examine the implementation of Islamic political ethics in Indonesia by referring to the thought of Ibn Khaldun. Humans as social beings cannot be separated from the political dimension of their lives, where ethics play an important role in the decision- making process and the management of society. In Islam, politics is seen as part of worship so that it must be based on religious principles. Ibn Khaldun emphasized the importance of the state running fairly and honestly based on religious morals and ethics to ensure development in various sectors of life. This research uses a qualitative approach with a literature study method, utilizing data sources from various literature, theories, research, and documents. Content analysis of Ibn Khaldun's works and related literature is used to explore the implementation of political ethics in Indonesia. The results show that the implementation of Islamic political ethics in Indonesia is guided by Pancasila as the basis of the state that reflects moral and ethical values in politics. The application of political ethics is expected to form a civilized, just, democratic, respectful and prosperous society.